By the way, I was wondering about this proof method. Would the following proof work?
x = 1 - (1 - (1 - (1 - \dots
x = 1 - x
x = 0.5
To shed some light, I'm an economist, not a mathematician. But I have used this method to prove the formula for a discounted stream of infinite cash flows:
NPV = 1 + \delta + \delta^2 + \ldots
NPV = 1 + \delta (1 + \delta + \ldots
NPV = 1 + \delta NPV
NPV = \frac{1}{1-\delta}
I guess it has to do with whether a series converges or not. If it doesn't you probably can't assume that x \in \mathbb{R}, or something like that.
Yes, this seems like a similar approach to prove your expression, replacing part of the infinite expression with itself. Not familiar with the economics part of it though ;)
x \in \mathbb{R}
, or something like that.